2016
DOI: 10.1186/s12985-016-0489-3
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of orf virus from sheep and goats in Ethiopia, 2008–2013

Abstract: BackgroundOrf is a contagious disease of sheep, goats and wild ungulates caused by orf virus (ORFV) a member of the genus Parapoxvirus, Poxviridae family. Although orf is endemic in Ethiopia, little attention has been given so far as it is not a notifiable disease by the World Organization for Animal Health. In this work, we have investigated orf outbreaks representing five different geographical locations of Ethiopia, in Amba Giorgis, Gondar zuria, Adet, Debre zeit and Adami Tulu, between 2008 and 2013.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 26 publications
3
40
0
Order By: Relevance
“…Although ORFV infections are self-limiting with low mortality rates, mortality rates of 20-90% have been reported in severe outbreaks (Scagliarini et al, 2012). The proliferative lesions around the mouth observed in this report are characteristic clinical presentation of Orf, which is not confirmatory, because such lesions are also seen in outbreaks of Peste des petits ruminants, Sheep pox (SPP) and goat pox (GTP) (Nandi et al, 2011;Gelaye et al, 2016). In this study, ORFV was detected by PCR in the scab, lymph node and spleen samples collected during the Orf outbreak which confirms the diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 42%
See 1 more Smart Citation
“…Although ORFV infections are self-limiting with low mortality rates, mortality rates of 20-90% have been reported in severe outbreaks (Scagliarini et al, 2012). The proliferative lesions around the mouth observed in this report are characteristic clinical presentation of Orf, which is not confirmatory, because such lesions are also seen in outbreaks of Peste des petits ruminants, Sheep pox (SPP) and goat pox (GTP) (Nandi et al, 2011;Gelaye et al, 2016). In this study, ORFV was detected by PCR in the scab, lymph node and spleen samples collected during the Orf outbreak which confirms the diagnosis of the disease.…”
Section: Discussionmentioning
confidence: 42%
“…It is caused by Orf virus (ORFV) (Gelaye et al, 2016). Orf virus belongs to the Genus Parapoxvirus, subfamily Chordopoxvirinae, family Poxviridae (Fleming et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For isolation of ORFV, primary lamb testes cell culture is most commonly used because of its high sensitivity (Kottaridi et al, 2006). However, Vero cell line has also been successfully used for ORFV isolation, and CPEs of ORFV were observed on days 3 and 5 after the first or second passage (Gelaye et al, 2016). In our study using the Vero cell line for virus isolation, CPEs were observed on the third passage, 5 days after inoculation.…”
Section: Discussionmentioning
confidence: 55%
“…Based on crust location, infected animals are usually disabled to graze and walk, which leads to weight and production loss. Also, secondary bacterial infections additionally worsen the lesions (Gelaye et al, 2016). The mortality rate in general is very high comparing to mortality rate which is generally low.…”
Section: Research Articlementioning
confidence: 99%
“…The primers used to amplify a fragment of the B2L gene of parapoxviruses [15] are indicated in Table 2.…”
Section: Sequencingmentioning
confidence: 99%